What does the American presidency mean? : the need for interpretation in presidency studies - Holtzman, Richard (Routledge series on interpretive methods, 2025)
"What Does the American Presidency Mean? The Need for Interpretation in Presidency Studies makes a compelling case for how interpretivism contributes to our understanding of the American presidency. This brief book is accessible and inviting, regardless of a reader's background in presidency studies or interpretivism. Part I explores several dimensions of interpretivist and positivist methodologies. Chapters discuss the characteristics of interpretivism, genealogically trace positivism's dominance in presidency studies, and identify how attributes of the presidency that raise methodological challenges for positivism are the same that make it fertile ground for interpretivism. Part II explores a wide range of interpretive scholarship on the American presidency, including studies of presidential meaning making, the institution's historical-political development, presidential symbolism, the construction of the presidency, and the presidential spectacle. The book concludes with an interpretation of recent developments emphasizing the timeliness, relevance, and importance of methodological pluralism in presidency studies. The book is written for anyone interested in the meaning of the presidency, whether scholars or graduate students in American political science, or those from other disciplines within and outside the United States. It is appropriate for courses on the American Presidency, Executive Politics, Political Communication, Rhetoric, and Social Science Methods among others"-- Provided by publisher.